2007
DOI: 10.1007/s10681-007-9503-6
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between hybrid performance and AFLP based genetic distance in highland maize inbred lines

Abstract: The objectives of this study were to determine the crossing performance of highland maize inbred lines for grain yield, days to silk and plant height; estimate genetic distance (GD) among the inbred lines and in association with tester parents, and to investigate the relationship of GD with hybrid performance and midparent heterosis (MPH). A total of 26 inbred lines were crossed with six (population and line) testers in a factorial-mating scheme. The F 1' s and the parents were evaluated at five locations in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
36
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 29 publications
9
36
1
1
Order By: Relevance
“…In this context, many authors have demonstrated practical applications for molecular marker techniques using restriction fragment length polymorphisms (RFLPs) (Ajmone-Marsan et al, 1998;Benchimol et al, 2000), amplified fragment length polymorphisms (AFLPs) (Oliveira et al, 2004;Legesse et al, 2007) and simple sequence repeats (SSRs) or microsatellites (Reif et al, 2003). Genetic analyses using either Wright's F-statistics or genetic distances remain the most common focus for the characterization of genetic differentiation (Latch et al, 2006;Bracco et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, many authors have demonstrated practical applications for molecular marker techniques using restriction fragment length polymorphisms (RFLPs) (Ajmone-Marsan et al, 1998;Benchimol et al, 2000), amplified fragment length polymorphisms (AFLPs) (Oliveira et al, 2004;Legesse et al, 2007) and simple sequence repeats (SSRs) or microsatellites (Reif et al, 2003). Genetic analyses using either Wright's F-statistics or genetic distances remain the most common focus for the characterization of genetic differentiation (Latch et al, 2006;Bracco et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between molecular marker distance and heterosis remains unclear. Some of the reports state significant association (Lanza et al, 1997;Amorim et al, 2006;Srdic et al, 2007) whereas, the others state non-significant or no association between markers based GD and heterosis (Shieh and Thseng, 2002;Legesse et al, 2008;Devi and Singh, 2011).…”
mentioning
confidence: 99%
“…Some authors have demonstrated the efficiency of the identification of heterotic groups of maize lines by using molecular procedures such as restriction fragment length polymorphisms (RFLPs) Benchimol et al, 2000;Pinto et al, 2003;Warburton et al, 2005), amplified fragment length polymorphisms (AFLPs) (Oliveira et al, 2004;Legesse et al, 2007) and simple sequence repeat (SSR) markers (Reif et al, 2003;Barata and Carena, 2006). An advantage over conventional methods is that few divergent lines are not discriminated, and consequently, heterotic groups are formed that contain genotypes, which unequivocally represent the differences in the allele frequency of the populations.…”
Section: Issn: 2319-7706 Volume 6 Number 6 (2017) Pp 61-73mentioning
confidence: 99%